Development of AI and IoT Based Microcontroller Simulator to Improve 4C Skills in learning - Wahyudi; Ahmad Risal; Muhammad Romario Basirung (Journal of Embedded Systems, Security and Intelligent Systems, 2025)
The development of digital technology demands mastery of 21st century skills, particularly the 4Cs (Critical Thinking, Creativity, Collaboration, Communication). However, conventional microcontroller learning is often limited to technical aspects without training these skills. This research aims to develop a microcontroller simulator based on AI (Artificial Intelligence) and IoT (Internet of Things) as an interactive media to improve 4C skills in digital technology learning. The research method uses a Research and Development (R&D) approach with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The simulator is designed with machine learning integration for learning difficulty adaptation and IoT for cloud-based project simulation. Validation was conducted through expert tests (pedagogy, AI, and embedded systems experts) and field trials on engineering students with questionnaire instruments, observations, and 4C skills tests. The results of the developed Simulator are proven to improve the understanding of microcontroller concepts while training 4C skills, with the following results: 1) Critical Thinking: Participants were able to analyse problems 25% faster through AI-based case simulation. 2) Creativity: There was a 30% increase in the variety of IoT project solutions generated. and 3) Collaboration & Communication: Teamwork effectiveness improved based on the collaboration rubric assessment. The implications of this research can be applied in technical education curriculum, vocational training, or STEM/STEAM development.